Comprehensive literature review of monkeypox. Issue 1 (31st December 2022) - Hatmal, Ma'mon M.; Al-Hatamleh, Mohammad A. I.; Olaimat, Amin N.; Ahmad, Suhana; Hasan, Hanan; Ahmad Suhaimi, Nurfatihah Azlyna; Albakri, Khaled A.; Abedalbaset Alzyoud, Anas; Kadir, Ramlah; Mohamud, Rohimah
ABSTRACT: The current outbreak of monkeypox (MPX) infection has emerged as a global matter of concern in the last few months. MPX is a zoonosis caused by the MPX virus (MPXV), which is one of the Orthopoxvirus species. Thus, it is similar to smallpox caused by the variola virus, and smallpox vaccines and drugs have been shown to be protective against MPX. Although MPX is not a new disease and is rarely fatal, the current multi-country MPX outbreak is unusual because it is occurring in countries that are not endemic for MPXV. In this work, we reviewed the extensive literature available on MPXV to summarize the available data on the major biological, clinical and epidemiological aspects of the virus and the important scientific findings. This review may be helpful in raising awareness of MPXV transmission, symptoms and signs, prevention and protective measures. It may also be of interest as a basis for performance of studies to further understand MPXV, with the goal of combating the current outbreak and boosting healthcare services and hygiene practices. Trial registration: ClinicalTrials.gov identifier: NCT02977715. . Trial registration: ClinicalTrials.gov identifier: NCT03745131. . Trial registration: ClinicalTrials.gov identifier: NCT00728689. . Trial registration: ClinicalTrials.gov identifier: NCT02080767. .